2022
DOI: 10.3389/fimmu.2022.965971
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, immunogenicity and safety of COVID-19 vaccines in older adults: a systematic review and meta-analysis

Abstract: BackgroundOlder adults are more susceptible to severe health outcomes for coronavirus disease 2019 (COVID-19). Universal vaccination has become a trend, but there are still doubts and research gaps regarding the COVID-19 vaccination in the elderly. This study aimed to investigate the efficacy, immunogenicity, and safety of COVID-19 vaccines in older people aged ≥ 55 years and their influencing factors.MethodsRandomized controlled trials from inception to April 9, 2022, were systematically searched in PubMed, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 107 publications
3
21
0
Order By: Relevance
“…Specific mRNA, viral-vector-based, and inactivated SARS-CoV-2 vaccines are being used worldwide. While efficacy of vaccines have been confirmed in adults 1 3 , there is a debate regarding the outcomes of vaccination in the elderly 4 , 5 . Several factors affect vaccine efficacy including age, prior antigen exposure, vaccine schedule, and vaccine dose 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Specific mRNA, viral-vector-based, and inactivated SARS-CoV-2 vaccines are being used worldwide. While efficacy of vaccines have been confirmed in adults 1 3 , there is a debate regarding the outcomes of vaccination in the elderly 4 , 5 . Several factors affect vaccine efficacy including age, prior antigen exposure, vaccine schedule, and vaccine dose 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen of 67 systematic reviews identified were relevant (Supplemental Table S1) and were cross-checked for articles to be included in abstract screening and full-text assessment. One prior systematic review identified had similar objectives to the current study (11) and all studies included in this prior review were included for full-text assessment. A total of 243 studies for full-text screening were identified from this first step.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…A total of 243 studies for full-text screening were identified from this first step. The main search was then conducted in the WHO COVID-19 Research Database to identify relevant studies published since the prior similar systematic review (11) S2.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omicron variants of SARS-CoV-2 have been related to reduced severity of illness and risk of death but increased incidence of breakthrough infections [1]. Primary and boosted vaccination against SARS-CoV-2 has also significantly reduced the risk for severe disease and death associated with COVID-19 [2][3][4][5], however, SARS-CoV-2 infection remains significant morbidity and mortality issue among the highly vulnerable populations including the elderly, immunocompromised people, and those with chronic diseases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%